Information giving in Malaysian breast cancer survivors' blogs: A thematic analysis / Wan Nur Asyura Wan Adnan Ab and Noor Aireen Ibrahim - Wan Adnan Ab, Wan Nur Asyura; Ibrahim, Noor Aireen (Universiti Teknologi MARA Cawangan Pahang, 2017)
Communicating online has become an essential human activity. This includes exchanging information and sharing experience related to health and illness in an online platform such as social media, forums and blogs. Breast cancer survivors’ blog is one of the growing sources of information which internet users sought. Past studies suggest that different kind of breast cancer information is shared through blogs from jargon-packed medical information written by professionals to lay medical information written by breast cancer survivors. Notwithstanding, little is known about what kind of information available in Malaysian breast cancer survivors’ blogs. The purpose of this paper is to examine the information provided by Malaysian breast cancer survivors through their blogs using thematic analysis. The data was drawn from three Malaysian breast cancer survivors’ blogs with a total of 240 blog postings. Atlas.ti software was used to analyse the data. The analysis yielded two main themes: Medical information giving related to breast cancer and non-medical information giving related to breast cancer. It is assumed that non-medical information related to breast cancer is the most predominant information throughout Malaysian breast cancer survivors’ blogs. It is also learned that information provided by Malaysian breast cancer survivors is not meant to challenge professional knowledge or assume an expert roles but it serves as an avenue to share experience, knowledge and raise awareness on breast cancer. The findings of this study provide an indication of the potential role of blogs as one of the platforms to disseminate health information in Malaysia.